Treatment outcomes and prognostic factors in patients with driver mutant non-small cell lung cancer and de novo brain metastases - Seda Kahraman; Serdar Karakaya; Muhammed Ali Kaplan; Sema Sezgin Goksu; Akin Ozturk; Zehra Sucuoglu Isleyen; Jamshid Hamdard; Sedat Yildirim; Tolga Dogan; Selver Isik; Abdussamet Celebi; Burcu Belen Gulbagci; et al. (Scientific Reports, 2024)
Abstract Central nervous system (CNS) metastases can be seen at a rate of 30% in advanced stages for patients with non-small cell lung cancer (NSCLC). Growing evidence indicates the predictive roles of driver gene mutations in the development of brain metastases (BM) in recent years, meaning that oncogene-driven NSCLC have a high incidence of BM at diagnosis. Today, 3rd generation targeted drugs with high intracranial efficacy, which can cross the blood–brain barrier, have made a positive contribution to survival for these patients with an increased propensity to BM. It is important to update the clinical and pathological factors reflected in the survival with real-life data. A multi-center, retrospective database of 306 patients diagnosed with driver mutant NSCLC and initially presented with BM between between November 2008 and September 2022 were analyzed. The median progression-free survival (mPFS) was 12.25 months (95% CI, 10–14.5). While 254 of the patients received tyrosine kinase inhibitor (TKI), 51 patients received chemotherapy as first line treatment. The median intracranial PFS (iPFS) was 18.5 months (95% CI, 14.8–22.2). The median overall survival (OS) was 29 months (95% CI, 25.2–33.0). It was found that having 3 or less BM and absence of extracranial metastases were significantly associated with better mOS and iPFS. The relationship between the size of BM and survival was found to be non-significant. Among patients with advanced NSCLC with de novo BM carrying a driver mutation, long-term progression-free and overall survival can be achieved with the advent of targeted agents with high CNS efficacy with more conservative and localized radiotherapy modalities.